Pengaruh Penggunaan Brand Ambassador terhadap Keputusan Pembelian pada Produk Oreo X Blackpink - Silviana Nurrizkiah (STIKes Ibnu Sina Ajibarang, 2024)
Based on data taken from the Top Brand Award, Oreo biscuit products always get the first position with the best brand assessment according to research conducted by Top Brand to Indonesian consumers. With Oreo winning the competition, it was discovered that Oreo used brand ambassadors for its products. The purpose of this study is to find out and analyze brand ambassadors on Oreo, to find out and analyze purchase decisions on Oreo products, to find out and analyze the influence of brand ambassadors on purchase decisions. The research conducted is a type of quantitative research. The sampling method used in this study uses nonprobability sampling by determining total sampling/census on 35 female Oreo consumer respondents, who have bought Oreo X Blackpink products 1 x and know Blackpink as Oreo brand ambassadors. The data collection technique uses questionnaires, observations, and literature studies. The data analysis technique used validity test, reliability test, normality test, heterokedasticity test, multicollinearity test, simple regression analysis, persial hypothesis test, t-test, simultaneous hypothesis test, f-test, and determination coefficient calculation.